The Evaluation Of The Teaching Performance Of The Teachers Of The Physical Education Department In The Institute Of Science And Techniques Of Physical And Sports Activities From The Point Of View Of The Second Year Master Students - سليماني, نورالدين (Université de M'sila, 2018)
This study aimed to determine the teaching performance of the teachers of the Physical Education Department of the Institute of Science and Techniques of physical and sports activities from the point of view of the second year master studentsand with its three axises , communication , the presentation and implementation of teaching in addition to the evaluation process ,and starting from the fact that The assessment process is generally necessary as an integral part of the development of in any vital area of the society, especially in the universities .The evaluation ofthe performance particularly in the educational institutions and the universities is important indicator to judge the extent to which the performance quality has been achieved ;since The university student is the most knowledgeable person and familiar with the university teacher who is considered as one of the cornerstones that based the the university and the responsible in activating the educational process within the institutions of higher education ;this enable him to judge his teaching performance properly . The study was intended to provide the opportunity for the university teachers and its administration to determine and encourage strengths, and to identify and treat the weaknesses By taking the point view of the second year Master students about the university teachers performance in the Department of Physical Education Institute of Science and Technology of physical activities and sports at the University of Mohammed Boudiaf Msila.Finally, to ensure that the measuring instrument used has the necessary psychometric characteristics. The study sample consisted of (72) second year Master students from the Department of Physical Education at the Institute of Science and Techniques of Physical and Sports Activities at the University of Mohammed Boudiaf in Msila, The questionnaire of the Evaluation of Teaching Performance was distributed,; and the descriptive approach was used. The current study reached several results, the most important of which are: ▪The existence of communication among teachers is one of the fundamental determinants of the the learning process success , and this is according to the view of the students because they are more familiar with the university teachers in general and the teachers of physical education in particular, which enables them to properly judge their teaching performance. ▪The university teachers are highly qualified to successfully present , implement and evaluate the teaching process .
Keywords: The assessment of the teaching performance ; the University teachers ; communication ; the teaching process presentation and implementation ; Assessment (evaluation) .